LINTAS: SISTEM SIMULASI LALU LINTAS MENGGUNAKAN SIMEVENTS MATLAB - ERWIN (POLITEKNIK PIKSI GANESHA, 2018)
Road traffic is a supporting medium that is essential to various means of landtransportation that connect various locations and even large cities. Smooth traffic is agood parameter of the management of a city, also as a sign to determine thetechnological and economic development in the city. As the rate of civilization grows, aswell as the number of people, the road traffic becomes more crowded, so that, congestionoccurs to an alarming level. The solution to breaking down the congestion problem is byapplying some methods and traffic engineering. However, implementing some methodsand traffic engineering without proper planning, will lead to high costs and less optimalresults.In this article we proposed a traffic simulation system called as